1176. Risk Factors for ESBL Enterobacteriaceae Colonization Identified by Universal Admission Screening in a London Teaching Hospital. (26th November 2018) - Batra, Rahul; Otter, Jonathan; Natale, Alex; Tosas, Olga; Dyakova, Eleonora; Edgeworth, Jonathan
Abstract: Background: Individual risk factors such as antibiotic use and foreign travel are typically associated with ESBL-producing Enterobacteriaceae (ESBL-E) carriage. Few studies have evaluated variations in community demographics or social and material deprivation as risk factors for ESBL-E carriage. Methods: All admissions to a London hospital group were screened for ESBL-E carriage from rectal swabs for four months in 2015. Patients completed a risk factor questionnaire, and those with a residential postcode in the catchment area were linked to a database containing community-based risk factor data. Risk factors for ESBL-E carriage were determined by binary logistic regression. Isolates that were ESBL-E phenotypically were confirmed by microarray (CT103XL Check-MDR, CheckPoint). The Check-MDR array simlutaneously detects common ESBL and carbapenemase genes, including plasmid-mediated AmpC. Genotypic ESBL-E were split into three groups: CTX-M-15 (Group 1), CTX-M-9 (Group 2), and other (Group 3) for further analysis. Results: Three hundred sixty (9.0%) of 4, 006 patients carried ESBL-E; of which, 1, 633 had a residential postcode within the catchment area. In multivariable analysis, risk factors for phenotypic ESBL-E carriage included travel to Asia (OR 5.0, CI 2.5–10.0) or Africa (OR 2.9, CI 1.2–7.0) in the past 12 months, and two or more courses of antibiotics in the past 6 months (OR 2.2, CI 1.5–3.4). Residence in an area with a high proportion of Arab residents and residence in an area with a low proportion of houses with two or more bedrooms were associated with ESBL-E carriage in univariable but not multivariable analysis. Risk factors for the three genotypic ESBL groups were broadly similar to the analysis of phenotypic ESBL carriage, although the number of days traveling abroad in the past 12 months was more associated with Group 1 (CTX-M-15) and Group 3 (other), and older age was associated with Group 3 (other) ESBLs. Conclusion: We linked individual risk factor information with community-based risk factor information, concluding that individual risk factors (including antibiotic use and overseas travel) were more important than community-based risk factors for predicting colonization with ESBL-E at the time of hospital admission. This information is useful when identifying risk groups for targeted screening. Disclosures: All authors: No reported disclosures.